The first experience of immunotherapy application of ipilimumab in combination with chemotherapy of small-cell lung cancer in the Russian population. Analysis of the combined data of two centers, participating in the multicenter randomized phase III study СА 184-156 - A E Kuzminov (Современная онкология, 2018)
Introduction. Patients with advanced small cell lung cancer (SCLC) have an extremely poor prognosis on the background of standard chemotherapy combination of etoposide and platinum-based drugs. In a randomized, double-blind of СА184-156 phase III study, the efficacy and safety of ipilimumab (immune checkpoint inhibitor) or placebo in combination with etoposide and platinum drugs were evaluated as the first-line therapy of disseminated SCLC. The article deals with the results of treatment of patients with advanced SCLC, who participated in the international multicenter phase III study CA184-156 in two Russian Research Centers: the Department of chemotherapy (33 patients) and the Department of diagnostic (23 patients) N.N.Blokhin National Medical Research Center of Oncology of the Ministry of Health of the Russian Federation. Materials and methods. Randomization of patients was carried out in a ratio of 1:1 in the group of therapy: etoposide + platinum drug (carboplatin or cisplatin) + ipilimumab and etoposide + platinum drug + placebo. Ipilimumab/placebo was administered at a dose of 10 mg/kg every 3 weeks in parallel with the third and fourth cycles of chemotherapy, further two administrations of ipilimumaba/placebo were performed at intervals of 3 weeks. Further, in the absence of progression, the maintenance therapy with ipilimumab/placebo was performed every 12 weeks. The main endpoints of the study were the assessment of progression-free survival (PFS) and overall survival (OS). Results. In the study CA184-156, the median PFS was 4.6 months in the chemotherapy group with ipilimumab (95% CI 4.5-5.0) and 4.4 months in the chemotherapy group with placebo (95% CI 4.4-4.6). There were no statistically significant differences. The analysis of 56 patients in the subgroup in our centers showed similar findings of median PFS: 4.4 and 4.3 months, respectivelyIn the study CA184-156, the median OS was 11 months in the chemotherapy group with ipilimumab (95% CI 10.5-11.3) and 10.9 months in the chemotherapy group with placebo (95% CI 10-11.5). There were no statistically significant differences. The analysis of 56 patients in the subgroup in our centers showed the following results: median OS was 9.7 months (95% CI 7.8-14) and 10.7 months (95% CI 6.5-20.1), respectively. The multifactorial analysis confirmed the significant effect of such factors as: ECOG 1/2 performance status and age on PFS, and ECOG 1/2 performance status and scheme of chemotherapy (etoposide + cisplatin/etoposide + carboplatin) on OS. Unexpected adverse events in the group of chemotherapy with ipilimumab were not noted. Conclusion. The addition of ipilimumab to chemotherapy did not contribute to an increase either in PFS or in OS in comparison with chemotherapy alone for advanced SCLC patients. Unexpected adverse events in the group of chemotherapy with ipilimumab were not noted. The study of the efficacy of ipilimumab in patients with disseminated SCLC in combination with PD1 inhibitors (nivolumab) is ongoing. The results obtained in the analysis of the data in the subgroups of patients, who participated in the study on the basis of the Department of chemotherapy (33 patients) and Department of diagnostic (23 patients) of N.N.Blokhin National Medical Research Center of Oncology of the Ministry of Health of the Russian Federation corresponded to the data received in the entire multicenter study CA184-156.